A comparison of inertial motion capture systems: DorsaVi and Xsens - Drapeaux, A.; Carlson, K. (International Journal of Kinesiology & Sports Science, 2020)
Background: dorsaVi Professional Suite, founded in 2018, is a 3D wearable sensor technology system that monitors the kinematic data of the lower extremity and lumbar spine. The dorsaVi system is used in the clinical setting to assist with clinical rehabilitation and preventive measures. Objective: The purpose of this study was to compare the inertial motion capture systems: the dorsaVi Professional Suite and Xsens to determine validity and reliability. Methods: This study utilized nine participants (7 female, 2 male) with data collected on two separate sessions. Each subject performed 15 repetitions each of double leg squats, left single leg squat, and right single leg squat during session one and then repeated the same testing procedure 7-10 days later. Kinematic variables measured were tibial inclination, knee varus, and knee valgus. Pearson product moment correlation coefficients were used to demonstrate the relationship within and between the motion capture systems across the knee positions and squat trials. Results: Within system reliability measurements demonstrated strong correlations (r>0.90) of the lower extremity kinematic data between testing sessions. Between system validity measurements also demonstrated strong correlations (r>0.90) across all lower extremity movements. Conclusions: The dorsaVi Professional Suite knee module kinematic data showed strong correlations to the validated motion capture system (Xsens). Thus, a clinician should be confident in using the dorsaVi in the evaluation, diagnosis, and treatment of patients.